Implementasi manajemen pembelajaran berbasis Contextual Teaching and Learning (CTL) dalam meningkatkan maharatul kalam dengan dukungan media quizizz - Jahra, Shofiyah Hafshoh Rabi`ah (Maliki Interdisciplinary Journal, 2026)
Low self-confidence and limited vocabulary remain the primary obstacles in maharatul kalam (speaking skills) instruction, while the integration of contextual learning management with gamified technology is still rarely explored in depth (research gap). This study aims to analyze the implementation of Contextual Teaching and Learning (CTL)-based management supported by Quizizz to enhance students’ speaking skills. The research object focuses on Arabic language learning at the Madrasah Tsanawiyah level utilizing a digital ecosystem. The method employed is descriptive qualitative analysis through literature studies and secondary data analysis. The results indicate that the systematic synergy between CTL management and Quizizz’s audio response and gamification features increases learning effectiveness to 80%, while simultaneously reducing language anxiety and strengthening functional mufrodat (vocabulary) mastery within real-world contexts. The implications of this study emphasize that successful Arabic language learning in the digital era depends not only on technological sophistication but also on the teacher’s managerial ability to align contextual materials with the utilization of adaptive technological features.